Probation Service in the Republic of Kazakhstan: experience of development (Journal of actual problems of jurisprudence, 2019)
By the legislation of the Republic of Kazakhstan is a comparative analysis of penal legislation United States, Britain, Japan, and,on this basis predicts further development and improvement of legislation of Kazakhstan on probation.